A ÓPERA DA FLORESTA OU A PELEJA DOS BOIS CONTRÁRIOS - Fernandes, José Guilherme dos Santos (Organon, 2007)
The different versions about the Amazonian are portrayed in several speeches about your cultural manifestations. This article intends to analyze those speeches about the bois-bumbás of the Parintins city (AM), and how those ones build the great speech about the popular culture in that area.